A randomized trial of grant writing coaching groups: Baseline analysis of early-career scientists’ research background, demographics, and mentorship variables - Anne Marie Weber-Main; Richard McGee; Melanie Steiner; Jeffrey Engler; Harlan P. Jones; Jessica M. Faupel-Badger; Alperen Korkmaz; Andrew K. Langi; Patrick O. Monahan; Kolawole S. Okuyemi (PLoS ONE, 2025)
Introduction Racial, ethnic, and gender disparities in academic career advancement persist in biomedical disciplines. One approach to addressing this problem is systematizing access to mentorship in critical skills such as grant writing. This report summarizes the baseline characteristics of early-career investigators who enrolled in a randomized trial of a group coaching intervention focused on National Institutes of Health (NIH) grant application development. Methods Surveys assessed participants’ demographic characteristics, research focus, prior publications and grant submissions, self-efficacy for grantsmanship and career advancement, and access to mentorship. Two-sided t-test and Fisher’s exact test were performed to compare baseline variables by gender identity (male/female) and by background from a racial or ethnic population that is an underrepresented minority group in biomedical research (non-URM/URM). Results The study sample includes 271 faculty and 96 postdoctoral fellows. Sixty-two percent of faculty and 76.0% of postdoctoral fellows identified as female. Nearly half (45.4% of faculty, 49.0% of postdocs) were from URM populations in biomedical research. At baseline, most were conducting clinical and translational research at institutions with high levels of research activity. Past submission of NIH R-series applications was limited; 29.9% of faculty had submitted K applications. On average, participants had moderate levels of self-efficacy (in grantsmanship and career advancement) and research-related mentoring support. Male and non-URM participants had a higher mean number of previous publications. For the remaining variables, there were no or minimal differences by gender identity and URM status. Conclusions Early-career investigators from diverse backgrounds are motivated to engage in external grant writing coaching programs regardless of existing mentorship and other supports at their home institutions, suggesting that grant coaching can provide complementary value.